Oxidative stability and iron and nickel migration into soybean oil heated in cookware of different materials - Diego Quintaes, Késia; Amaya-Farfan, Jaime; Morgano, Marcelo Antônio; Almeyda Haj-Isa, Niurka Maritza (Grasas y Aceites, 2007)
Cookware may release some inorganic components into foods during cooking, some of which have undesirable consequences. In fried foods, for instance, oil oxidation is favored by metals. The present study evaluated oxidative stability (AOCS method) and iron and nickel migration (inductively coupled plasma-optical emission spectrometry) into refined soybean oil in four cycles, with intervals of 24 hours. The cookware materials were glass, aluminum, stainless steel, iron and soapstone. The results demonstrated that the lowest metal migration occurred from glass and aluminum pans while the oil heated in these pans showed the highest oxidative stability. The highest migration of Fe and Ni into the oil occurred from the soapstone and iron pots (3.94 and 3.21 mg _ kg-1, respectively).Nevertheless, increasing loss of oxidative stability was evident in the oils heated in the soapstone, stainless steel and iron cookware, in this order. Since iron migration was lower from glass and aluminum pans, these were considered the best type of materials for frying